Uji Daya Hambat Antibakteri Fungi Endofit Kulit Jeruk Nipis (Citrus aurantifolia) Terhadap Bakteri Staphylococcus aureus - Muhammad Azdar Setiawan; Hasnawati Hasnawati; Sernita Sernita; Lisa Sulistia (Fakultas Farmasi Universitas Andalas, 2016)
Endophytic fungi is fungi that lives within plant tissue and it is not harm to the plant it self. Endophytic fungi can produce a substance potencial to be antibacteria. This research aimed to test the antibacterial effect of endophytic fungi that has been isolated from lime skin Citrus auranti folia of Staphylococcus aureus. The methods that has been used to test antibacterial effect was paper disc method, done by gluing paper disc containing of endophytic fungi in agar combination media that has been smear with Staphylococcus aureus. The result of this researh is both endophytic fungi has effect as antibacterial against Staphylococcus aureus, but the type II of endophytic fungi has more effective and stronger antibacterial effect compare to endophytic fungi type I.